Risk Transfer and the insurance industry. (Global Financial Stability Report; Global Financial Stability Report, 2004)
This paper focuses on risk transfer and discusses the insurance sector, particularly life insurers. It expands on issues raised in previous Global Financial Stability Reports by asking whether financial stability has benefited or could benefit from insurers' broader participation in credit markets, including credit derivatives. The paper assesses the impact on financial stability of life insurers' investment behavior and risk management in the largest mature markets. It highlights that the policy implications differ from market to market, and may offer useful lessons to emerging market countries with developing capital markets.